(untitled) (Communications in Mathematical Research, 2021)
In this paper, the concept of weighted possibilistic mean of interval-valued fuzzy number is first introduced. Further, the notions of weighted possibilistic variance, covariance and correlation of interval-valued fuzzy numbers are presented. Meantime, some important properties of them and relationships between them are studied.